2016
DOI: 10.1016/j.ijgo.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Fetal middle cerebral artery Doppler indices and clinical application at Korle Bu Teaching Hospital, Accra, Ghana

Abstract: The reference curve for the peak systolic velocity increases with gestational age, whereas the other indices decrease in a parabolic pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…At this time, the brain is not well developed, the blood vessels are slender, and the resistance is high. To ensure brain development, the MCA-PI decreases significantly at 37 to 41 +6 weeks, [10,11] as observed in the neonates without acidosis in the present study. When fetal hypoxia occurs, blood flow is redistributed to ensure the brain's blood supply (the “brain protective effect”).…”
Section: Discussionsupporting
confidence: 60%
“…At this time, the brain is not well developed, the blood vessels are slender, and the resistance is high. To ensure brain development, the MCA-PI decreases significantly at 37 to 41 +6 weeks, [10,11] as observed in the neonates without acidosis in the present study. When fetal hypoxia occurs, blood flow is redistributed to ensure the brain's blood supply (the “brain protective effect”).…”
Section: Discussionsupporting
confidence: 60%
“…For example, the top three most cited studies (those of Arduini and Rizzo 24 , Baschat and Gembruch 25 and Acharya et al 26 ) show an important risk of bias owing to the fact that they are only the sixth, eleventh and ninth ranked studies based on methodological quality according to a recently published systematic review 18 . It could be argued that older studies are more likely to be cited than are more recent ones with higher-quality methodology because the results of newer studies might not have had sufficient time to be incorporated into clinical practice 52 .…”
Section: This Is the First Systematic Review To Analyze The Impact Ofmentioning
confidence: 99%
“…Comparison of PI of UA, PI of MCA, and CPR as a percentage of pregnancy for our guinea pig data and human published studies (Medina-Castro et al [ 24 , 25 ], Parra-Cordero et al [ 26 ], Arduini et al [ 27 ], Seffah et al [ 28 ], Bahlmann et al [ 29 ], Morales-Roselló et al [ 30 ], Ebbing et al [ 31 ], and Baschat et al [ 32 ], previously summarized in Oros et al 2019 [ 20 ]) are shown in Figure 7 D–F. This analysis revealed that, in both guinea pig and human datasets, UA PI decreased across pregnancy, with a tendency to stabilize in the last third of pregnancy ( Figure 7 D).…”
Section: Resultsmentioning
confidence: 67%